Development of smart apps creator learning media on pancasila material as life value in the fifth-grade of elementary school - Efendi, Ulfa Putri; Muhammadi, Muhammadi (Program Studi Pendidikan Guru Sekolah Dasar, FKIP, Universitas Riau, 2023)
This research is motivated by the lack of use technology-based Pancasila Education learning media can stimulate students in learning. The purpose of this study was to determine the validity and practicality of the developed media. This type of research is development research (Research and Development) with the ADDIE model. The results of the validity test on Smart Apps Creator media obtained a percentage 96.66% with a very valid category, the results of the material validity test 90.76% with a very valid category, and the results of the media validity test were 96% with a very valid category. While the results of the practicality test in the trial school obtained a percentage of 92.85% with a very practical category for the teacher response questionnaire and 94.46% for the student response questionnaire with a very practical category. The results of the practicality test in the research school 96.42% with a very practical category for the teacher response questionnaire and 93.06% with a very practical category for the student response questionnaire. It can be concluded that the Smart Apps Creator learning media on the material of Pancasila as a way of life in class IV integrated elementary school has been valid and practical.